Circulating metabolites and general cognitive ability and dementia: Evidence from 11 cohort studies. Issue 6 (6th January 2018) - van der Lee, Sven J.; Teunissen, Charlotte E.; Pool, René; Shipley, Martin J.; Teumer, Alexander; Chouraki, Vincent; Melo van Lent, Debora; Tynkkynen, Juho; Fischer, Krista; Hernesniemi, Jussi; Haller, Toomas; Singh‐Manoux, Archana; et al.
Abstract: Introduction: Identifying circulating metabolites that are associated with cognition and dementia may improve our understanding of the pathogenesis of dementia and provide crucial readouts for preventive and therapeutic interventions. Methods: We studied 299 metabolites in relation to cognition (general cognitive ability) in two discovery cohorts (N total = 5658). Metabolites significantly associated with cognition after adjusting for multiple testing were replicated in four independent cohorts (N total = 6652), and the associations with dementia and Alzheimer's disease (N = 25, 872) and lifestyle factors (N = 5168) were examined. Results: We discovered and replicated 15 metabolites associated with cognition including subfractions of high‐density lipoprotein, docosahexaenoic acid, ornithine, glutamine, and glycoprotein acetyls. These associations were independent of classical risk factors including high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol, triglycerides, glucose, and apolipoprotein E ( APOE ) genotypes. Six of the cognition‐associated metabolites were related to the risk of dementia and lifestyle factors. Discussion: Circulating metabolites were consistently associated with cognition, dementia, and lifestyle factors, opening new avenues for prevention of cognitive decline and dementia.